Pengaruh Pengalaman Kerja, Pelatihan dan Lingkungan Kerja Terhadap Pengembangan Karir Karyawan (Studi Kasus Karyawan Pt. Bina Pratama Sakatojaya) - Mayroza Wiska; Putri, Dini Elida; Oktavia, Yusra (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research aims to test or analyze the influence that work experience, training and work environment have on employee career development. The analytical method in this research is to use a quantitative method by collecting questionnaire data. The respondents used as samples in this research were taken from employees of PT. Bina Pratama Sakatojaya has 52 employees. The type of data used in this research is primary data, the data collection method used was a questionnaire and processed using SPSS 20. Based on the T test, it shows that the work experience variable has a positive and significant effect on career development, training has a negative and significant effect on career development, and the environment. work has a positive and significant effect on career development. Based on the F test, the results obtained show that together the variables of experience, training and work environment have a significant influence on career development. Based on the determinant coefficient (R2), it shows that work experience, training and work environment on career development is 95.7%, while 4.3% is influenced by other factors not included in this research model..